Prevalence and predictors of postpartum depression among postnatal women in Lagos, Nigeria - EO, Adeyemo; EO, Oluwole; OJ, Kanma-Okafor; OM, Izuka; KA, Odeyemi (African health sciences, 2020)
Background: Globally, postpartum depression is one of the most common but often unrecognized complications of childbirth, yearly affecting about 10–15% of postnatal women. This study aimed to determine the prevalence of postpartum depression and its predictors among postnatal women in Lagos. Methods: A descriptive cross-sectional study was conducted among 250 mothers in Eti-Osa Local Government Area of Lagos State, Nigeria, attending six Primary Health Care centers for infant immunization at six weeks post-delivery. Data was collected using a pretested semi-structured interviewer administered questionnaire which included the Edinburgh Postnatal Depression Scale. Analysis was carried out using SPSS version 23TM. Chi-square and logistic regression analyses were used to determine associations and predictive relationships between various factors and the presence of postpartum depression. The level of significance was set at <0.05. Results: The prevalence of postpartum depression was 35.6%. Multiparity, delivery by cesarean section, mother being unwell after delivery, and not exclusively breastfeeding the baby were the factors linked with postpartum depression. Following multiple logistic regression, having postpartum blues (p=0.000; OR=32.77; 95%CI=7.23-148.58)., not getting help with caring for the baby (p=0.008; OR=2.64; 95%CI=1.29-5.42), experiencing intimate partner violence (p=0.000; OR=5.2; 95%CI=2.23-11.91) and having an unsupportive partner (p=0.018; OR=2.6; 95%CI=1.17-5.78) were identified as predic- tors of postpartum depression. Conclusion: This study revealed a high prevalence of postpartum depression, identifying both the obstetric and psycho- social predictors. Social support for women both in the pre- and postnatal periods and routine screening of women for postpartum depression should be encouraged for early detection and immediate intervention. Keywords: Postpartum depression; PPD; Eti-Osa; postnatal women; Lagos.